2017
DOI: 10.1002/hep4.1056
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic lipophagy: New insights into autophagic catabolism of lipid droplets in the liver

Abstract: The liver is a central fat‐storage organ, making it especially susceptible to steatosis as well as subsequent inflammation and cirrhosis. The mechanisms by which the liver mobilizes stored lipid for energy production, however, remain incompletely defined. The catabolic process of autophagy, a well‐known process of bulk cytoplasmic recycling and cellular self‐regeneration, is a central regulator of lipid metabolism in the liver. In the past decade, numerous studies have examined a selective form of autophagy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 108 publications
(195 reference statements)
1
55
0
Order By: Relevance
“…In a highly selective form of LD-targeted autophagy, referred to as "lipophagy," the specific turnover of LDs occurs through the action of acid lipases deposited into the autolysosome (Kaur and Debnath, 2015). Lipophagy thus represents an alternative to conventional cytosolic lipase-driven LD breakdown (Weidberg et al, 2009;Singh and Cuervo, 2012;Liu and Czaja, 2013;Schulze et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a highly selective form of LD-targeted autophagy, referred to as "lipophagy," the specific turnover of LDs occurs through the action of acid lipases deposited into the autolysosome (Kaur and Debnath, 2015). Lipophagy thus represents an alternative to conventional cytosolic lipase-driven LD breakdown (Weidberg et al, 2009;Singh and Cuervo, 2012;Liu and Czaja, 2013;Schulze et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, an increasing number of studies have shown that dysregulation of lipophagy plays a pathogenetic role in the development of NAFLD, and that all the steps of this process can be affected (Patrick and Lake, 1969;Kwanten et al, 2014;Martinez-Lopez and Singh, 2015;Schulze et al, 2017). Notably, a previous study analyzed the accumulation of p62/SQTSM1 as marker of autophagy blockage in hepatocytes of NAFLD patients (Fukushima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids are mainly generated by selective autophagy of lipid droplets (lipophagy), while amino acids are generated by proteolysis through autophagy and are used for gluconeogenesis. 33,37 Therefore, autophagy plays a decisive role in regulating liver physiology and balancing liver metabolism. 38 Chronic alcohol intake or excessive energy intake causes damage to the regulation of autophagy.…”
Section: Definition Of Autophagymentioning
confidence: 99%